Contemporary musical expressions in Canada - Hoefnagels, Anna; Klassen, Judith, 1976-; Johnson, Sherry, 1968- (McGill-Queen's University Press, 2019)
"Music and dance in Canada today are diverse and expansive, reflecting histories of travel, exchange and interpretation, and challenging conceptions of expressive culture that are bounded and static. Reflecting current trends in ethnomusicology, Contemporary Musical Expressions in Canada examines cultural continuity, disjuncture, intersection, and interplay in music and dance across the country. Essays reconsider conceptual frameworks through which cultural forms are viewed, critique policies meant to encourage crosscultural sharing, and address ways in which traditional forms of expression have changed to reflect new contexts and audiences. From North Indian kathak dance, Chinese lion dance, early Toronto hip hop, and contemporary cantor practices within the Byzantine Ukrainian Church in Canada to folk music performances in twentieth-century Quebec, Gaelic milling songs in Cape Breton, and Mennonite songs in rural Manitoba, this collection offers detailed portraits of contemporary music practices and how they engage with diverse cultural expressions and identities. At a historical moment when identity politics, multiculturalism, diversity, immigration, and border crossings are debated around the world, Contemporary Musical Expressions in Canada demonstrates the many ways that music and dance practices in Canada engage with these broader global processes."--